Description of Duttaphrynus atukoralei (Anura: Bufonidae) tadpoles from Sri Lanka - Bopage, Malaka M.; Wewelwala, Krishan; Krvavac, Milivoje; Jovanovic, Olga (Zootaxa, 2015)
Duttaphrynus atukoralei (Bogert & Senanayake, 1966) is a relatively abundant toad known from Southern and Southeastern Sri Lanka. It occurs from sea level up to ~200 m above sea level (IUCN 2014). For almost half a century since its original description there was no information on its life cycle; the only information available is related to its description and distribution (Dutta & Manamendra-Arachchi 1996; Manamendra-Arachchi & Pethiyagoda 2006).